Piezoelectricity Evolution and Future of a Technology - Heywang, Walter; Lubitz, Karl.; Wersing, Wolfram; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
Discovered in 1880, piezoelectric materials play a key role in an innovative market of several billions of dollars. Recent advances in applications derive from new materials and their development, as well as to new market requirements. With the exception of quartz, ferroelectric materials are used for they offer both high efficiency and sufficient versatility to meet adequately the multidimensional requirements for application. Consequently, strong emphasis is placed on tailoring materials and technology, whether one deals with single crystals, ceramics or plastic materials. Tailoring requires a basic understanding of both physical principles and technical possibilities and limitations. This report elucidates these developments by a broad spectrum of examples, comprising ultrasound in medicine and defence industry, frequency control, signal processing by SAW-devices, sensors, actuators, including novel valves for modern motor management. It delivers a mutual fertilization of technology push and market pull that should be of interest not only to materials scientists or engineers but also to managers who dedicate themselves to a sound future-oriented R&D policy.
Basics and Materials -- Basic Material Quartz and Related Innovations -- The Role of Ferroelectricity for Piezoelectric Materials -- Piezoelectric PZT Ceramics -- Relaxor Ferroelectrics -- Piezoelectric Polymers and Their Applications -- Applications and Innovations -- Electromechanical Frequency Filters -- Ultrasonic Imaging -- High Effective Lead Perovskite Ceramics and Single Crystals for Ultrasonic Imaging -- High-Power Ultrasound Transducers for Therapeutic Applications -- Piezoelectric Motors and Transformers -- Piezoelectric Positioning -- Piezoelectric Injection Systems -- Advanced RF Signal Processing with Surface Acoustic Waves on Piezoelectric Single Crystal Substrates -- Piezoelectric Films for Innovations in the Field of MEMS and Biosensors -- Piezoelectric Composites by Solid Freeform Fabrication: A Nature-Inspired Approach -- Characterisation Methods -- Microstructural Analysis Based on Microscopy and X-Ray Diffraction -- Small Signal Resonance Methods -- Large Signal Resonance and Laser Dilatometer Methods -- Ferroelastic Characterization of Piezoelectrics -- Multiscale Modelling -- First-Principles Theories of Piezoelectric Materials -- Thermodynamic Theory -- Effective Medium Theories -- Finite-Element Modelling of Piezoelectric Actuators: Linear and Nonlinear Analyses -- The Future -- Trends in Ferroelectric/Piezoelectric Ceramics.
Keywords: Physics; Condensed matter; Engineering; Electronics; Microelectronics; Structural materials; Physics; Condensed Matter Physics; Engineering, general; Electronics and Microelectronics, Instrumentation; Structural Materials; Electronic books